Transformasi Ekonomi Lokal Menuju Ekonomi Digital: Strategi Pemberdayaan Melalui Seminar Literasi Digital - Sari, Ni Kadek Wahyuni Merta; Anam, Ahmad Gautsul; Mahfuz, Muhammad; Farisi, Moh Salman Al; Uli, Aprilla Sinta (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The transformation of the local economy toward a digital economy is a strategic step to enhance competitiveness and promote inclusive and sustainable economic growth, especially amidst the rapid development of information technology. This article discusses how digital literacy seminars can serve as an educational medium to strengthen the capacity of local communities—particularly micro, small, and medium enterprises (MSMEs)—in adopting digital technologies. Using a descriptive-qualitative approach, the seminar activities were observed to evaluate changes in participants’ understanding of economic digitalization concepts. The results showed a significant increase in participants' digital literacy levels and interest in utilizing digital technology in economic activities. This article concludes that educational interventions such as seminars can form an essential foundation for building a local digital economy ecosystem.